(untitled) (Philology, 2026)
The purpose of this paper is to introduce the use of realia during the acquisition of German at levels A1-A2 for students with different cultural backgrounds. The study looks at two aspects of the topic: which translations are used in the language books for Hungarian students and which methods and transfer operations the teacher has to use for the semanticization of realia for students from different cultural areas in German-English-Hungarian relations. The research methods used are text corpus analysis and guideline-based interviews with German language learners. The study shows the importance of using culture-specific vocabulary at a beginner level through listening activities, reading, and oral and written interaction. The most effective method of realia’s semanticization proves to be explicitation. Effective intercultural competence necessitates knowledge of culture-specific terms and idiomatic expressions.